2022
DOI: 10.3389/fmicb.2022.1008110
|View full text |Cite
|
Sign up to set email alerts
|

High diversity of Rickettsia spp., Anaplasma spp., and Ehrlichia spp. in ticks from Yunnan Province, Southwest China

Abstract: Rickettsia, Anaplasma, and Ehrlichia belonging to the order Rickettsiales are causative agents of tick-borne diseases in humans. During 2021, 434 ticks including Rhipicephalus microplus and R. haemaphysaloides were collected from three sampling sites in Yunnan Province, Southwest China, and analyzed for the presence of these bacteria. Nine bacterial species were identified, including two Rickettsia spp., three Anaplasma spp., and four Ehrlichia spp., some of which are potential human pathogens. Genetic and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Moreover, Candidatus Rickettsia jingxinensis, also named Candidatus Rickettsia longicornii ( Guo et al., 2019 ), was detected in H. longicornis and R. microplus ticks from Zigui County. This finding was not unexpected because it is a widely distributed spotted fever group Rickettsia species and has previously been detected in R. microplus and H. longicornis ticks from multiple provinces in China ( Guo et al., 2019 ; Wang et al., 2021 ; Lu et al., 2022 ). Additionally, two spotted fever group Rickettsia species— Ca.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, Candidatus Rickettsia jingxinensis, also named Candidatus Rickettsia longicornii ( Guo et al., 2019 ), was detected in H. longicornis and R. microplus ticks from Zigui County. This finding was not unexpected because it is a widely distributed spotted fever group Rickettsia species and has previously been detected in R. microplus and H. longicornis ticks from multiple provinces in China ( Guo et al., 2019 ; Wang et al., 2021 ; Lu et al., 2022 ). Additionally, two spotted fever group Rickettsia species— Ca.…”
Section: Discussionsupporting
confidence: 64%
“…It is surprising that Ca. Rickettsia jingxinensis, a spotted fever group Rickettsia frequently detected in ticks ( Guo et al., 2019 ; Wang et al., 2021 ; Lu et al., 2022 ), was identified in one C. tritaeniorhynchus sample. Natural infection of mosquitoes with Ca.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, Candidatus Rickettsia shennongii was identified in H. spinigera nymphs. This species was previously been reported as the causative agent of spotted fever in Rhipicephalus haemaphysaloides ticks in China [ 22 ]. Rickettsia spp.…”
Section: Discussionmentioning
confidence: 99%
“…The Rickettsia and Anaplasmataceae were detected targeting the 16S rRNA gene, while Borrelia was screened targeting the aB ( agellin B) gene. For precise identi cation, the gltA and groEL (60 kDa chaperonin) sequences were ampli ed from the Rickettsia, Ehrlichia, and Anaplasma strains detected in this study using primers as shown [8,9]. Furthermore, 16S rRNA sequences (approximately 1200 bp) were ampli ed from the Borrelia strains [9], and gltA sequences (approximately 400 bp) were ampli ed from the Candidatus Lariskella strains [8].…”
Section: Molecular Detection and Identi Cation Of The Pathogensmentioning
confidence: 98%
“…The DNA samples were screened for the presence of Rickettsia, Anaplasmataceae (Anaplasma spp., Ehrlichia spp., etc), and Borrelia bacteria using primers as shown previously, generating PCR products with a size of approximately 900 bp, 450 bp, and 400 bp, respectively [8, 9,10]. The Rickettsia and Anaplasmataceae were detected targeting the 16S rRNA gene, while Borrelia was screened targeting the aB ( agellin B) gene.…”
Section: Molecular Detection and Identi Cation Of The Pathogensmentioning
confidence: 99%